Fast Catalytic Esterification Using a Hydrophobized Zr‐MOF with Acidic Ionic Liquid Linkers. Issue 3 (20th January 2020) - Xu, Zichen; Zhao, Guoying; Hedin, Niklas; Xu, Mengmeng; Liu, Jiahui; Ullah, Latif; Zhang, Suojiang
Abstract: A Zr‐MOF with an acidic ionic liquid linker ([bpyH][CF3 SO3 ]) were externally hydrophobized with polydimethylsiloxane (PDMS) via a vapor deposition method (denoted as PDMS@UiO‐67‐CF3 SO3 ). The morphology of UiO‐67‐CF3 SO3 was well maintained after PDMS coating, and PDMS had little effect on the chemical properties of UiO‐67‐CF3 SO3, while the hydrophobicity of the surface of UiO‐67‐CF3 SO3 was improved greatly as demonstrated by water contact angle measurement. The derived hydrophobized PDMS@UiO‐67‐CF3 SO3 exhibited excellent catalytic performance in the esterification of acetic acid and isooctyl alcohol, it only needed 4 h to reach the reaction equilibrium, while for UiO‐67‐CF3 SO3, it was 18 h. The decrease in reaction time was mainly attributed to the accelerated the removal of water and isooctyl acetate, resulting the increase rate in the forward reaction. In addition, in the other esterification of acids and alcohols, PDMS@UiO‐67‐CF3 SO3 also showed good catalytic performance. Abstract : The outer of UiO‐67‐CF3 SO3 is covered with PDMS hydrophobic layer that will accelerate the removal of the products of the esterification of acetic acid and isooctyl alcohol and reduce the reaction time significantly.